2015
DOI: 10.1007/s11255-015-1039-4
|View full text |Cite
|
Sign up to set email alerts
|

Can body mass index predict survival outcomes in patients treated with radical nephroureterectomy for upper-tract urothelial carcinoma?

Abstract: Our study results are inconclusive, in that, the multivariate analysis did not identify the influence of BMI on survival, although higher BMI appears clinically associated with favorable survival outcomes in Korean patients with UTUC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Similarly, other retrospective studies confirmed the prognostic value of higher BMI in patients with both BC or UTUC [23,24] while another series suggested that also lowest value of BMI was associated to worst oncological outcomes [25]. On the contrary, other retrospective studies failed to find an association between BMI and oncological outcomes after surgery [26,27] while other confirmed a prognostic role only after RC without significant association after RNU [28,29]. Due to the absence of external and perspective validation of the results observed in retrospective series, the role of BMI in oncological outcomes prediction after surgery still remains unclear.…”
Section: Obesity and Risk Of Urothelial Cancermentioning
confidence: 85%
“…Similarly, other retrospective studies confirmed the prognostic value of higher BMI in patients with both BC or UTUC [23,24] while another series suggested that also lowest value of BMI was associated to worst oncological outcomes [25]. On the contrary, other retrospective studies failed to find an association between BMI and oncological outcomes after surgery [26,27] while other confirmed a prognostic role only after RC without significant association after RNU [28,29]. Due to the absence of external and perspective validation of the results observed in retrospective series, the role of BMI in oncological outcomes prediction after surgery still remains unclear.…”
Section: Obesity and Risk Of Urothelial Cancermentioning
confidence: 85%
“…In this study, BMI was not significantly associated with CSS and OS. Similarly, the prognostic roles of decreased BMI in UTUC patients have been inconclusive in previous studies . This may partly be because BMI does not reflect body composition, including the proportion of fat to muscle tissue and the degree of fluid accumulation such as ascites and edema .…”
Section: Discussionmentioning
confidence: 96%
“…When UI was defined as a tumour located only in the ureter (subgroup 1) or as a tumour located only in the ureter and as a dominant lesion in that location (subgroup 2), no differences in OS were found. Sensiti vi ty analysis indicated that the study of Kim et al affected the summary result in the first subgroup [24]. Heterogeneity: τ 2 = 0.00; χ 2 = 1.30, df = 2 (p = 0.52); I 2 = 0% Test for overall effect: Z = 6.10 (p = 0.00001) Total (95% Cl) 100.0% 1.39 [1.11, 1.74] Heterogeneity: τ 2 = 0.07; χ 2 = 31.20, df = 7 (p < 0.0001); I 2 = 78% Test for overall effect: Z = 2.86 (p = 0.004) Test for subgroup differences: χ 2 = 9.13, df = 2 (p = 0.01 ), I 2 = 78.1%…”
Section: Resultsmentioning
confidence: 98%
“…The 14 studies in this meta-analysis included 14,895 participants [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The baseline characteristics of the included studies are summarised in Table I study ranged from 133 to 3387 (mean 1064, median 623).…”
Section: Resultsmentioning
confidence: 99%